2014
DOI: 10.5999/aps.2014.41.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Microsurgery Optimization

Abstract: The increased application of the da Vinci robotic platform (Intuitive Surgical Inc.) for microsurgery has led to the development of new adjunctive surgical instrumentation. In microsurgery, the robotic platform can provide high definition 12×-15× digital magnification, broader range of motion, fine instrument handling with decreased tremor, reduced surgeon fatigue, and improved surgical productivity. This paper presents novel adjunctive tools that provide enhanced optical magnification, micro-Doppler sensing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…Studies have investigated the possibilities for robot‐assisted microsurgery in surgeon training (Alrasheed, Liu, Hanasono, Butler, & Selber, ; Brahmbhatt, Gudeloglu, Liverneaux, & Parekattil, ; Gudeloglu, Brahmbhatt, & Parekattil, ; Kotsougiani et al, ; Liverneaux, Hendriks, Selber, & Parekattil, ; Selber & Alrasheed, ). Furthermore, studies have reported the utility of robot‐assisted microvascular anastomosis through animal experiments (Katz, Rosson, Taylor, & Singh, ; Knight et al, ; Liverneaux, Taleb, Nectoux, & Facca, ; Taleb, Nectoux, & Liverneaux, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated the possibilities for robot‐assisted microsurgery in surgeon training (Alrasheed, Liu, Hanasono, Butler, & Selber, ; Brahmbhatt, Gudeloglu, Liverneaux, & Parekattil, ; Gudeloglu, Brahmbhatt, & Parekattil, ; Kotsougiani et al, ; Liverneaux, Hendriks, Selber, & Parekattil, ; Selber & Alrasheed, ). Furthermore, studies have reported the utility of robot‐assisted microvascular anastomosis through animal experiments (Katz, Rosson, Taylor, & Singh, ; Knight et al, ; Liverneaux, Taleb, Nectoux, & Facca, ; Taleb, Nectoux, & Liverneaux, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 68 studies included in this review, only three used a robotic system other than the daVinci ® . This dominance is beginning to be challenged and while equipment additions such as a micro-forcep is currently available for the daVinci ® robot and external companies have developed micro-doppler probes and hydrojet dissectors ( 91 ) it will be the development of further microsurgical instruments that will allow greater use of the robot in the field of plastic and reconstructive surgery. The combination of motion scaling and tremor-free instrument manipulation with new instrument design will also allow new avenues in microsurgery that have to date been too technically demanding to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Various tools make it possible to see beyond the mere external appearance, revealing functional properties. [1] Some systems enable to form an additional image that reveals microcirculation and therefore make it easier to distinguish cancerous tissue from healthy tissue by the injection of a small amount of indocyanine green, a dye tracer visualized by an infrared system. This noninvasive technique also verifies the effectiveness of a vascular anastomosis.…”
Section: Functionalized Visionmentioning
confidence: 99%